Beyond solutionist science for the Anthropocene: To navigate the contentious atmosphere of solar geoengineering. (April 2019) - Asayama, Shinichiro; Sugiyama, Masahiro; Ishii, Atsushi; Kosugi, Takanobu
The emerging narrative of the Anthropocene has created a new space for changes in global environmental change (GEC) science. On the one hand, there is a mounting call for changing scientific practices towards a solution-oriented transdisciplinary mode that can help achieve global sustainability. On the other hand, the scientists' desire to avoid exceeding planetary boundaries has broken a taboo on researching solar geoengineering, a dangerous idea of deliberately cooling the Earth's climate. Whilst to date the two features have been discussed separately, there is a possible confluence in the future. This paper explores this close yet precarious relationship between transdisciplinary GEC science and solar geoengineering in the context of Future Earth, a new international platform of Earth system science. Our aim is to understand how a transdisciplinary mode of science can navigate the contention over solar geoengineering and its course of research without breeding polarization. By seeking the immediacy of 'problem-solving', Future Earth is drawn into the solutionist thinking that orders the mode of engagement in pursuing consensus. However, because conflict is inescapable on the solar geoengineering debate, transdisciplinary engagement might as well aim at mapping out plural viewpoints and allowing people to disagree. In transdisciplinary engagement, as co-design signifies the engagement of stakeholders with decision-making in science, a fair and transparent procedure of making decisions is also needed. From our own experience of co-designing research priorities, we suggest that, if carefully designed, voting can be a useful tool to mediate the contentious process of transdisciplinary decision-making with three different benefits for collective decision-making, namely, efficiency, inclusivity and learning . For the future directions of transdisciplinary GEC science, since the Anthropocene challenges are truly uncertain and contentious, it is argued that the science for the Anthropocene should move away from a solutionist paradigm towards an experimentalist turn.